Preparation method of YAG (yttrium aluminum garnet) derived glass optical fiber based on transparent ceramic with multilayer composite structure
Through the dry press forming and vacuum sintering process of multi-layer composite structure transparent ceramics, combined with the molten core wire drawing method, the problems of high cost of YAG fiber core rods and difficult component adjustment are solved, and efficient and stable preparation of YAG derived glass fibers are achieved. , suitable for broadband fiber lasers.
Patent Information
- Application Number
- CN202411462136.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, when preparing YAG derived glass fibers, the YAG single crystal block is costly and has a long cycle. The ceramic core rod is prone to introduce impurities and pores, and it is difficult to effectively adjust the fiber components, resulting in poor roundness and concentricity of the fiber.
Multi-layer composite structure transparent ceramic is used as the preformed rod core rod for optical fiber drawing, and is prepared by dry press molding and vacuum sintering processes, combined with the molten fiber core wire drawing method to achieve co-doping and component adjustment of different rare earth ions.
It realizes flexible adjustment of the co-doping concentration of rare earth ions, improves the roundness and concentricity of the optical fiber, reduces the preparation cost and cycle, improves the matching and stability of the optical fiber, and is suitable for broadband fiber lasers.
Smart Images

Figure CN119263623A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of advanced functional ceramics and optical fiber preparation, and in particular to a method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic. Background Art
[0002] Yttrium aluminum garnet (YAG) is a laser matrix material with excellent comprehensive properties and is suitable for doping with a variety of active ions (Ce 3+ , Yb 3+ Cr 4+ , Er 3+ ). In recent years, rare earth ion-doped YAG-derived glass optical fibers based on rare earth ion-doped YAG crystals or ceramics and prepared by the melt-in-tube (MIT) method have attracted wide attention in the field of single-frequency / mode-locked fiber lasers. The cladding of this type of optical fiber is composed of quartz glass, and the core is composed of yttrium aluminum silicate glass, which has a good match with traditional commercial quartz optical fibers. In addition, since the core is a component with high Al2O3 and Y2O3 content, it can be doped with a higher concentration of rare earth ions, which is conducive to obtaining higher gain, and has better thermal conductivity and stimulated Brillouin scattering threshold.
[0003] The process of preparing YAG-derived glass optical fiber by fused core method is similar to the traditional tube-rod method, which can be roughly divided into two main steps: preparation of optical fiber preform and optical fiber drawing. Figure 1 As shown. Among them, the preparation of optical fiber preform is the most critical step in the preparation process of YAG-derived glass optical fiber. The preform used for the preparation of YAG-derived glass optical fiber consists of two parts: the outer cladding and the core rod. The outer cladding is quartz glass, and the core rod can usually be selected as YAG single crystal or YAG ceramic. The preparation process usually involves cutting and grinding YAG single crystal or YAG ceramic into long strips of set diameter and length as the core rod, and drilling a hole in the center of the quartz glass rod according to the set diameter and depth as the outer cladding, and then placing the core rod in the cladding glass tube to form an optical fiber preform.
[0004] The preparation cost of YAG single crystal block is high, the cycle is long, and the composition control range is narrow. Ordinary fired YAG ceramics often introduce impurities and pores inside, which has many disadvantages in research and production as the core rod of optical fiber preform. Compared with traditional single crystals and ceramics, YAG transparent ceramics have the advantages of low production cost, high rare earth doping concentration, and flexible structural design. It has great advantages as the core rod of optical fiber preform.
[0005] The preparation of YAG-derived glass optical fiber doped with multiple rare earth ions by fused core method has been one of the research hotspots in recent years. At present, there are two main methods for preparing YAG-derived glass optical fibers doped with multiple rare earth ions using YAG crystals or ceramics as preform core rods: one is to directly co-dope rare earth elements when preparing crystal or ceramic raw materials. The preform core rods obtained by this method have limited doping flexibility and can only be regulated in terms of composition; the other is to simply splice the prepared preform core rods with different rare earth doping, which can quickly achieve any combination of multiple different rare earths and has a higher degree of freedom in adjusting the composition of the preform core rods. However, during the fiber drawing process, the bonding and matching between the core interfaces of the composite structure are not good, resulting in poor roundness and concentricity of the drawn optical fiber. For details, see the article "Wei, ZS, Luan, J, Huang, L, et al. Single-frequency fiber laser of 315mW at 1940nm based on a Tm:YAG / Ho:YAG-co-derived silica fiber. Optics Letters, 2023, 48(19): 5109-5112". At present, there are also some new methods to realize the preparation of rare earth ion co-doped preform core rods. For example, in 2022, Zheng Baoluo's team used the UV-curing nanopowder method to prepare the core rod for the first time and successfully prepared Er / Yb co-doped YAG optical fiber. For details, see the article "Zheng, BL, Qi, FX, Yang, J, et al. Er:YAG / Yb:YAG nanopowders-derived Er / Yb co-dopedyttrium aluminosilicate (YAS) fibers fabricated by UV-curable nanocomposites for 1.5-μm single-frequency fiber lasers. Journal of the American Ceramic Society, 2022, 105: 7064-7071", and the corresponding patent application "Patent application number: CN202210051751.0, named: A method for preparing doped YAG-derived glass optical fiber", but the preparation cost of this method is high and the process flow is relatively cumbersome and complicated.
[0006] In recent years, diversified composite structure transparent ceramics have emerged. Using multi-layer composite structure transparent ceramics as laser materials can promote the uniform distribution of heat inside the material, inhibit heat accumulation, and help obtain high-efficiency, high-power, and high-beam quality laser output. For example, the YAG / Nd:YAG / YAG multi-layer structure ceramic rod prepared by Liu Wenbin and others from Shanghai Jiaotong University has a pump threshold of 23W at 1064nm, a pump power of 201W, an output power of 20.3W, a light conversion efficiency of 10.1%, and a scattering loss of 0.038cm -1 , the absorption loss is about 0.005cm -1 For details, see "Liu Wenbin. Preparation, microstructure and laser performance of Nd:YAG transparent ceramics. Shanghai Jiaotong University, 2012". Li Jiang et al. from Shanghai Institute of Silicates successfully prepared non-porous and dense YAG / Nd:YAG / YAG transparent ceramics by vacuum sintering using solid phase method. The optical transmittance of the sample reached 80.2% at 1064nm laser wavelength, and the maximum absorption peak was located at 808nm. Using 1000mW LD end-face pumping scheme, 8mW continuous laser output was obtained, and the slope efficiency was 4.0%. For details, see the article "Li J, Wu Y, Pan Y, et al. Laminar-structured YAG / Nd:YAG / YAG transparent ceramics for solid-state lasers. International Journal of Applied Ceramic Technology, 2008, 5(4): 360-364". However, the traditional YAG crystal prepared by solid phase method cannot effectively adjust the fiber components.
[0007] At present, the research on multi-rare earth ion co-doped YAG optical fiber is still at a very cutting-edge stage, and there are few related reports. No research has been found or retrieved that uses multi-layer composite structure YAG transparent ceramics as the fiber core and adopts the molten core drawing method to prepare YAG-derived glass optical fiber. Summary of the invention
[0008] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic, wherein the multi-layer composite structure YAG transparent ceramic of the preform core rod for optical fiber drawing is prepared by dry pressing and vacuum sintering process, and then the prepared multi-layer composite structure YAG transparent ceramic is prepared into a core rod by cutting and grinding and combined with a quartz tube to form a preform for optical fiber drawing, and finally the molten core drawing method is used to prepare the YAG-derived glass optical fiber. The multi-layer composite structure YAG transparent ceramic of the present invention can be used as a preform core rod for optical fiber drawing to achieve co-doping of different rare earth ions, which makes up for the deficiency that traditional YAG crystals and ceramic core rods cannot effectively adjust the optical fiber components.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The invention discloses a method for preparing YAG-derived glass optical fiber based on multi-layer composite structure transparent ceramics, wherein the multi-layer composite structure YAG transparent ceramics are used as core rods, which are placed in a quartz glass tube as cladding to form an optical fiber preform, and then the optical fiber preform is drawn into a YAG-derived glass optical fiber by a molten core drawing method (Melt-In-Tube, MIT).
[0011] The method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic specifically comprises the following steps:
[0012] (1) Preparation of multi-layer composite structure YAG transparent ceramics
[0013] (1.1) Preparation of multi-layer composite structure YAG transparent ceramic powder
[0014] Use high-purity aluminum oxide Al2O3, yttrium oxide Y2O3 and rare earth ion oxide according to the ideal chemical formula of rare earth ion doped YAG Er 3x Y 3(1-x) Al5O 12 Ingredients, 0<x≤0.2; wherein the rare earth ion oxide is selected from one of Er2O3, Nd2O3, Yb2O3, Er2O3, Tm2O3, Dy2O3, La2O3, Sm2O3; and sintering aids MgO 0.05-0.20wt.% and TEOS 0.2-0.8wt.% are prepared based on the total mass of Al2O3, Y2O3 and the rare earth ion oxide; and uniform rare earth ion doped multilayer composite structure YAG transparent ceramic powder is obtained by ball milling, drying and sieving with a sieve below 200#;
[0015] (1.2) Forming of multi-layer composite structure YAG transparent ceramic body
[0016] The uniform rare earth ion-doped multilayer composite structure YAG transparent ceramic powder prepared in step (1.1) is layered and flatly filled in an axial pressing mold according to the designed thickness of each layer, and is preliminarily pressed with a pressing parameter of 8-12 MPa for 25-35 seconds to obtain a preliminarily formed multilayer composite structure ceramic green body; then, cold isostatic pressing is performed with a pressing parameter of 180-220 MPa for 8-12 minutes to further compact the preliminarily formed ceramic green body to obtain a uniform and dense multilayer composite structure ceramic green body, with a green body density of >60%;
[0017] (1.3) Sintering of multi-layer composite structure YAG transparent ceramics
[0018] The uniform and dense multi-layer composite structure ceramic green body obtained in step (1.2) is subjected to vacuum sintering to obtain a multi-layer composite structure YAG transparent ceramic. The specific parameters are: vacuum degree ≤ 10 -3 Pa; heating rate 5±2℃ / min to 800℃±30℃, then 1℃ / min to 1780℃±50℃; stop heating, sinter at this temperature for 6-10h; then cool down to 300℃±30℃ at 5±2℃ / min and cool naturally;
[0019] (1.4) Annealing of multi-layer composite structure YAG transparent ceramics
[0020] The multi-layer composite structure YAG transparent ceramic obtained in step (1.3) is annealed in air or oxygen atmosphere to eliminate defects and stress in the ceramic. After annealing, double-sided optical polishing is performed multiple times. Specific parameters of annealing treatment: heating rate 5±2℃ / min to 1450±50℃ and heat preservation for 8-12h; cooling rate 5±2℃ / min to 300℃±30℃ and then naturally cooling;
[0021] (2) Preparation of YAG-derived glass optical fiber preform
[0022] (2.1) Preparation of preform cladding: High-purity quartz glass is selected and processed into a cylindrical glass tube with a central hole. The inner and outer surfaces are polished to a mirror finish, thus obtaining a centrally-through high-purity quartz glass tube as the cladding;
[0023] (2.2) Preparation of preform core rod: cutting, polishing and cleaning the multi-layer composite structure YAG transparent ceramic obtained in step (1) according to the design requirements to prepare the core rod of the optical fiber drawing preform rod;
[0024] (2.3) Preform assembly: seal one end of the through hole in the high-purity quartz glass tube, fill the core rod into the high-purity quartz glass tube, and then seal the other end of the through hole in the glass tube to form an optical fiber preform;
[0025] (3) Melt drawing of YAG-derived glass optical fiber
[0026] The assembled optical fiber preform is placed in a graphite furnace drawing tower for drawing. During the drawing process, argon gas is passed through the drawing furnace for protection. The drawing temperature is 2000℃-2050℃. The optical fiber diameter is adjusted by the glass tube feeding speed and the optical fiber traction wheel speed parameters, and finally a continuous YAG-derived glass optical fiber is obtained.
[0027] The specific parameters of the step (1.2) are: preliminary pressing, the pressing parameters are: 10MPa, 30s, to obtain a preliminary formed multi-layer composite structure ceramic green body; then cold isostatic pressing is adopted, the pressing parameters are: 200MPa, 10min.
[0028] The specific parameters of the step (1.3) are: heating to 800°C at a rate of 5°C / min, then heating to 1780°C at a rate of 1°C / min; stopping heating, sintering at this temperature for 8h; then cooling to 300°C at a rate of 5°C / min, and then cooling naturally.
[0029] The specific parameters of the annealing treatment in the step (1.4) are as follows: heating at a rate of 5°C / min to 1450°C and keeping the temperature for 10 hours; cooling at a rate of 5°C / min to 300°C and then cooling naturally.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) In step (1) of the present invention, the multi-layer composite structure YAG transparent ceramic of the preform core rod for optical fiber drawing is prepared by dry pressing and vacuum sintering process, and the rare earth ion doping concentration and doping type can be flexibly changed according to the demand, thereby effectively adjusting the components of YAG derived glass optical fiber; dry pressing has high production efficiency and short cycle, and can realize the complex structure forming of the preform core rod for optical fiber. Compared with the existing technology of simply splicing the preform core rods with different rare earth doping, the YAG transparent ceramic layer of the multi-layer composite structure has stronger bonding force and higher composite degree, and has good matching. The different doping layers have similar thermal expansion coefficients, which is helpful to draw YAG derived glass optical fiber with higher roundness and concentricity. Such optical fiber can be widely used in the field of broadband fiber lasers.
[0032] (2) In step (2) of the present invention, the prepared multi-layer composite YAG transparent ceramic is cut and ground into a core rod, which is then combined with a quartz tube to form a preform rod for optical fiber drawing. The YAG-derived glass optical fiber is prepared by a molten core drawing method. Compared with the YAG single crystal core rod, the core rod of the multi-layer composite YAG transparent ceramic greatly reduces the expensive preparation cost and the long production cycle of the single crystal block, thereby improving the preparation efficiency. Compared with YAG powder as the core rod, it makes up for the defects of more gaps between powder particles during the drawing process and more bubbles are easily generated in the high-temperature molten state, thereby improving the stability and operability of the experiment, and can stably and continuously prepare YAG-derived glass optical fibers.
[0033] In summary, compared with the prior art, the present invention uses the multi-layer composite structure YAG transparent ceramic as the core rod, and has excellent matching effect between the core and the cladding during the high-temperature drawing process. It can draw a YAG-derived glass optical fiber with high roundness and concentricity, good flexibility and thermodynamic stability that can be applied to fiber lasers, and has advantages in high efficiency, stability and operability. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of the principle of the fused core drawing method (Melt-In-Tube, MIT), where: Figure 1 (a) is a schematic diagram of preparing an optical fiber preform; Figure 1 (b) Schematic diagram of high-temperature melt drawing.
[0035] Figure 2 The present invention is a flow chart of the preparation method.
[0036] Figure 3 The molding and structural diagram of the multi-layer composite structure ceramic prepared by the present invention. Among them, Figure 3 (a) is a schematic diagram of axial compression + isostatic pressing of ceramic green body; (b-1) - (b-4) are schematic diagrams of the prepared 1-layer, 2-layer, 3-layer and 4-layer composite structures, respectively; (c-1) is a schematic diagram of the ceramic green body, (c-2) schematic diagrams of single-layer and double-layer composite structure YAG transparent ceramic samples, (c-3) side view of double-layer composite structure YAG transparent ceramic sample.
[0037] Figure 4 This is a graph showing the optical transmittance of the composite structure ceramic prepared in Example 1 of the present invention.
[0038] Figure 5 This is a physical picture of preparing an optical fiber preform rod according to an embodiment of the present invention, wherein: Figure 5 (a) is a schematic diagram of ceramic core rod processing; (b) is a schematic diagram of quartz cladding processing; (c) is a schematic diagram of preform rod assembly.
[0039] Figure 6 This is a real picture of optical fiber drawing in an embodiment of the present invention, wherein: Figure 6 (a) is a schematic diagram of a preform rod used for optical fiber drawing; (b) is a schematic diagram of an optical fiber drawing tower; (c-1) is a schematic diagram of a YAG-derived glass optical fiber, and (c-2) is a schematic diagram of an optical fiber end face. DETAILED DESCRIPTION
[0040] In order to better understand the present invention, the technical solution of the present invention is further explained below in conjunction with examples, but the implementation methods of the present invention are not limited thereto. For process parameters not particularly described, conventional techniques can be used.
[0041] Embodiment 1
[0042] A method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic. This embodiment is a method for preparing a YAG-derived glass optical fiber based on an Er:YAG / Yb:YAG double-layer composite structure transparent ceramic, including the preparation of an Er:YAG / Yb:YAG double-layer composite structure transparent ceramic for core rod preparation, the preparation of a YAG-derived glass optical fiber preform rod, and the melt drawing of a YAG-derived glass optical fiber.
[0043] like Figure 2 As shown, the preparation method of Er:YAG / Yb:YAG double-layer structure transparent ceramic YAG-derived glass optical fiber comprises the following steps:
[0044] (1) Preparation of Er:YAG / Yb:YAG double-layer structure transparent ceramics:
[0045] (1.1) Preparation of Er:YAG / Yb:YAG double-layer transparent ceramic powder:
[0046] The composition formula is as follows:
[0047] Composition of Er:YAG ceramic layer (Er doping concentration 3at.%):
[0048] Al2O3: 50.980g; Y2O3: 65.711g; Er2O3: 3.443g; MgO:
[0049] 0.096g; TEOS: 0.600g.
[0050] Composition of Yb:YAG ceramic layer (Yb doping concentration 3at.%):
[0051] Al2O3: 50.980g; Y2O3: 65.711g; Yb2O3: 3.547g; MgO:
[0052] 0.096g; TEOS: 0.601g.
[0053] The required raw materials were dried at 120°C for 12 hours to remove the moisture absorbed during storage; then, high-purity powder raw materials were weighed according to the component formula and ball-milled for 24 hours; the ball-milled slurry was thoroughly dried at 80°C, and then the powder was passed through a 200# sieve to obtain Er:YAG and Yb:YAG transparent ceramic raw material powders respectively.
[0054] (1.2) Forming of double-layer composite structure YAG transparent ceramic body: (refer to Figure 3 (shown)
[0055] The Er:YAG powder and Yb:YAG powder in step (1.1) are spread and filled in the dry pressing mold according to the designed thickness of each layer. Figure 3 In (a), the axial pressing is performed under a force of 10 MPa for 30 seconds to obtain a preliminary formed ceramic body; after the axial pressing is completed, the mold is demolded, and then the dense ceramic body is obtained by cold isostatic pressing at 200 MPa for 10 minutes. Figure 3 (b-2), (c-1), (c-2)(c-3) in it.
[0056] (1.3) Sintering of double-layer composite structure YAG transparent ceramics:
[0057] The green body formed in step (1.2) was vacuum sintered at 1780°C for 8 hours. The specific parameters were: vacuum degree ≤ 10 -3 Pa; heating rate 5℃ / min to 800℃, 1℃ / min to 1780℃; sintering temperature 1780℃, 8h; cooling rate 5℃ / min to 300℃ and then naturally cooling.
[0058] (1.4) Annealing of double-layer composite structure YAG transparent ceramics:
[0059] The ceramic sintered in step (1.3) is annealed in air or oxygen atmosphere to eliminate defects and stress in the ceramic. Specific parameters of annealing treatment: heating rate 5℃ / min to 1450℃; keeping at 1450℃ for 10h; cooling rate 5℃ / min to 300℃ and then cooling naturally. Figure 4 , is an optical transmittance curve of the Er:YAG / Yb:YAG double-layer structure transparent ceramic prepared in this embodiment. In the wavelength range of 300nm-2000nm, the base transmittance of the ceramic is >80%.
[0060] In the wavelength range of 300nm-2000nm, the ceramic reference transmittance is >80%.
[0061] (2) Preparation of YAG-derived glass optical fiber preform:
[0062] (2.1) Preparation of preform cladding, refer to Figure 5 (b) in:
[0063] The material is high-purity quartz glass, which is processed into a through cylindrical glass tube with an inner diameter of 3mm, an outer diameter of 20mm, and a length of 150mm. The inner and outer surfaces are polished to a mirror finish, and then the high-purity quartz glass tube is cleaned and dried multiple times using dilute hydrochloric acid, anhydrous alcohol, etc. for subsequent use.
[0064] (2.2) Preparation of preform core rod, refer to Figure 5 (a) in:
[0065] The double-layer composite structure YAG transparent ceramic prepared in step (1) is cut into 3×3 mm rectangular columns using a diamond cutting machine, and ground and polished to a thickness of 2.8 mm according to the size of the central hole of the glass tube. The prepared core rod is then ultrasonicated in a dilute hydrochloric acid solution for 5 minutes, and then washed with alcohol several times and dried to prepare a core rod for assembly into an optical fiber drawing preform rod.
[0066] (2.3) Preform assembly, refer to Figure 5 (c) in:
[0067] Use hydrogen-oxygen flame and quartz thin rod to seal one end of the center hole of the glass tube, fill the multi-layer composite structure YAG transparent ceramic preform core rod into the center hole of the glass tube, and then use hydrogen-oxygen flame and quartz thin rod to seal the other end of the center hole of the glass tube to form an optical fiber preform. Figure 1 (a) in .
[0068] (3) Melt drawing of YAG-derived glass optical fiber:
[0069] Reference Figure 1 (b) and Figure 6 In (a), (b), (c-1), and (c-2), the assembled optical fiber preform is fixed in a graphite furnace drawing tower for drawing. During the drawing process, argon gas and cooling water are always introduced for protection, and the drawing temperature is controlled at 2030°C.
[0070] When the temperature and fiber state are stable, the glass of the optical fiber preform is in a viscous flow state, while the fiber core in the center hole of the glass tube is in a molten state. After hot drawing, the optical fiber naturally cools and solidifies to form a continuous glass cladding and YAG optical fiber. The fiber diameter is adjusted by the glass tube feeding speed and the fiber traction wheel speed parameters, and finally a continuous YAG-derived glass optical fiber is obtained with good flexibility and thermodynamic stability.
[0071] Example 2
[0072] A method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic. This embodiment is a method for preparing a YAG-derived glass optical fiber based on a three-layer composite structure transparent ceramic Er:YAG / Tm:YAG / Er:YAG, including the preparation of Er:YAG / Tm:YAG / Er:YAG three-layer composite structure transparent ceramic for core rod preparation, the preparation of a YAG-derived glass optical fiber preform rod and the melt drawing of a YAG-derived glass optical fiber.
[0073] like Figure 2 As shown, the preparation method of the transparent ceramic YAG-derived glass optical fiber based on the Er:YAG / Tm:YAG / Er:YAG three-layer structure includes the following steps:
[0074] (1) Preparation of Er:YAG / Tm:YAG / Er:YAG three-layer structure transparent ceramics:
[0075] (1.1) Preparation of Er:YAG / Tm:YAG / Er:YAG three-layer structure transparent ceramic powder:
[0076] The composition formula is as follows:
[0077] Composition of Er:YAG ceramic layer (Er doping concentration 10at.%):
[0078] Al2O3: 50.980g; Y2O3: 60.969g; Er2O3: 11.476g; MgO:
[0079] 0.095g; TEOS: 0.617g.
[0080] Composition of Tm:YAG ceramic layer (Tm doping concentration 10at.%): Al2O3: 50.980
[0081] g; Y2O3: 60.969g; Tm2O3: 11.576g; MgO: 0.095g; TEOS:
[0082] 0.618g.
[0083] The required raw materials were dried at 120°C for 12 hours to remove the moisture absorbed during storage; then, high-purity powder raw materials were weighed according to the component formula and ball-milled for 24 hours; the ball-milled slurry was thoroughly dried at 80°C, and then the powder was passed through a 200# sieve to obtain Er:YAG and Tm:YAG transparent ceramic raw material powders respectively.
[0084] (1.2) Forming of three-layer composite structure YAG transparent ceramic body: (refer to Figure 3 (shown)
[0085] The Er:YAG powder and Tm:YAG powder in step (1.1) are layered and filled in the dry pressing mold according to the designed thickness of each layer, and axial pressing is performed under a force of 12MPa for 28s to obtain a preliminary formed ceramic body. After axial pressing, demolding is performed, and then cold isostatic pressing is performed at 180Mpa for 12min to obtain a dense ceramic body. Figure 3 (b-3) in.
[0086] (1.3) Sintering of three-layer composite structure YAG transparent ceramics:
[0087] The ceramic green body formed in step (1.2) is vacuum sintered at 1800°C for 8 hours. The specific parameters are: vacuum degree ≤ 10 - 3 Pa; heating rate 6℃ / min to 820℃, 1℃ / min to 1800℃; sintering temperature 1800℃, 8h; cooling rate 4℃ / min to 320℃ and then naturally cooling.
[0088] (1.4) Annealing of three-layer composite structure YAG transparent ceramics:
[0089] The ceramic sintered in step (1.3) is annealed in air or oxygen atmosphere to eliminate defects and stress in the ceramic. Specific parameters of the annealing treatment: heating rate 7°C / min to 1500°C; keeping at 1500°C for 10 hours; cooling rate 6°C / min to 310°C and then cooling naturally.
[0090] (2) Preparation of YAG-derived glass optical fiber preform:
[0091] (2.1) Preparation of preform cladding:
[0092] The material is high-purity quartz glass, which is processed into a through cylindrical glass tube with an inner diameter of 3mm, an outer diameter of 25mm, and a length of 150mm. The inner and outer surfaces are polished to a mirror finish, and then the high-purity quartz glass tube is cleaned and dried multiple times using dilute hydrochloric acid, anhydrous alcohol, etc. for subsequent use.
[0093] (2.2) Preparation of preform core rod:
[0094] The three-layer composite structure YAG transparent ceramic prepared in step (1) is cut into 3×3 mm rectangular columns using a diamond cutting machine, and ground and polished to a diameter of 2.8 mm according to the size of the central hole of the glass tube. The prepared core rod is then ultrasonicated in a dilute hydrochloric acid solution for 5 minutes, and then washed with alcohol several times and dried to prepare a core rod for assembly into an optical fiber drawing preform rod.
[0095] Reference Figure 1In (a), one end of the central hole of the glass tube is sealed with an oxyhydrogen flame and a thin quartz rod, a multi-layer composite structure YAG transparent ceramic preform core rod is placed in a slender glass guide tube for subsequent feeding, and the other end of the central hole of the glass tube is sealed with an oxyhydrogen flame and a thin quartz rod.
[0096] (3) Melt drawing of YAG-derived glass optical fiber, see Figure 1 (b) in:
[0097] ①Fix the hollow quartz glass tube in the graphite furnace drawing tower for drawing. During the drawing process, argon gas and cooling water circulation protection are always introduced, and the drawing temperature is controlled at 2030℃.
[0098] ② When the temperature and fiber state are stable, the quartz glass tube is in a viscous flow state. At this time, the prepared core rod is put into the center hole of the glass tube. The fiber core is in a molten state at high temperature. After hot drawing, the fiber is naturally cooled and solidified to form a continuous glass cladding and YAG fiber. The fiber diameter is adjusted by the glass tube feeding speed and the fiber traction wheel speed parameters, and finally a continuous YAG-derived glass optical fiber is obtained, which has good flexibility and thermodynamic stability.
[0099] Embodiment 3
[0100] Referring to the process of Example 1 or 2, the ceramic components and the number of layers in Example 1 or 2 can be flexibly changed according to technical requirements, and multi-layer composite structure YAG transparent ceramics with different doping degrees and number of layers can be prepared as core rods. Figure 3 (b-1)-(b-4) can be used to prepare one-layer, two-layer, three-layer and four-layer YAG transparent ceramics respectively, and even more layers of YAG transparent ceramics can be prepared by the same process, which have good flexibility and thermodynamic stability.
Claims
1. A method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic, characterized in that: A multi-layer composite structure YAG transparent ceramic is used as a core rod and placed in a quartz glass tube as a cladding to form an optical fiber preform. The optical fiber preform is then drawn into a YAG-derived glass optical fiber using the Melt-In-Tube (MIT) method.
2. A method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic, characterized in that: The specific steps include: (1) Preparation of multi-layer composite structure YAG transparent ceramics (1.1) Preparation of multi-layer composite structure YAG transparent ceramic powder Use high-purity aluminum oxide Al2O3, yttrium oxide Y2O3 and rare earth ion oxide according to the ideal chemical formula of rare earth ion doped YAG Er 3x Y 3(1-x) Al5O 12 Ingredients, 0<x≤0.2; then prepare sintering aids MgO 0.05-0.20wt.% and TEOS 0.2-0.8wt.% based on the total mass of Al2O3, Y2O3 and rare earth ion oxide; mix by ball milling, dry, and sieve with a sieve below 200# to obtain a uniform rare earth ion-doped multi-layer composite structure YAG transparent ceramic powder; (1.2) Forming of multi-layer composite structure YAG transparent ceramic body The uniform rare earth ion-doped multilayer composite structure YAG transparent ceramic powder prepared in step (1.1) is layered and flatly filled in an axial pressing mold according to the designed thickness of each layer, and is preliminarily pressed with a pressing parameter of 8-12 MPa for 25-35 seconds to obtain a preliminarily formed multilayer composite structure ceramic green body; then, cold isostatic pressing is performed with a pressing parameter of 180-220 MPa for 8-12 minutes to further compact the preliminarily formed ceramic green body to obtain a uniform and dense multilayer composite structure ceramic green body, with a green body density of >60%; (1.3) Sintering of multi-layer composite structure YAG transparent ceramics The uniform and dense multi-layer composite structure ceramic green body obtained in step (1.2) is subjected to vacuum sintering to obtain a multi-layer composite structure YAG transparent ceramic. The specific parameters are: vacuum degree ≤ 10 -3 Pa; heating rate 5±2℃ / min to 800℃±30℃, then 1℃ / min to 1780℃±50℃; stop heating, sinter at this temperature for 6-10h; then cool down to 300℃±30℃ at 5±2℃ / min and cool naturally; (1.4) Annealing of multi-layer composite structure YAG transparent ceramics The multi-layer composite structure YAG transparent ceramic obtained in step (1.3) is annealed in air or oxygen atmosphere to eliminate defects and stress in the ceramic. After annealing, double-sided optical polishing is performed multiple times. Specific parameters of annealing treatment: heating rate 5±2℃ / min to 1450±50℃ and heat preservation for 8-12h; cooling rate 5±2℃ / min to 300℃±30℃ and then naturally cooling; (2) Preparation of YAG-derived glass optical fiber preform (2.1) Preparation of preform cladding: High-purity quartz glass is selected and processed into a cylindrical glass tube with a central hole. The inner and outer surfaces are polished to a mirror finish, thus obtaining a centrally-through high-purity quartz glass tube as the cladding; (2.2) Preparation of preform core rod: cutting, polishing and cleaning the multi-layer composite structure YAG transparent ceramic obtained in step (1) according to the design requirements to prepare the core rod of the optical fiber drawing preform rod; (2.3) Preform assembly: seal one end of the through hole in the high-purity quartz glass tube, fill the core rod into the high-purity quartz glass tube, and then seal the other end of the through hole in the glass tube to form an optical fiber preform; (3) Melt drawing of YAG-derived glass optical fiber The assembled optical fiber preform is placed in a graphite furnace drawing tower for drawing. During the drawing process, argon gas is passed through the drawing furnace for protection. The drawing temperature is 2000℃-2050℃. The optical fiber diameter is adjusted by the glass tube feeding speed and the optical fiber traction wheel speed parameters, and finally a continuous YAG-derived glass optical fiber is obtained.
3. The method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic according to claim 2, characterized in that: The rare earth ion oxide is selected from one of Er2O3, Nd2O3, Yb2O3, Er2O3, Tm2O3, Dy2O3, La2O3, and Sm2O3.
4. The method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic according to claim 2, characterized in that: The specific parameters of the step (1.2) are: preliminary pressing, the pressing parameters are: 10MPa, 30s, to obtain a preliminary formed multi-layer composite structure ceramic green body; then cold isostatic pressing is adopted, the pressing parameters are: 200MPa, 10min.
5. The method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic according to claim 2, characterized in that: The specific parameters of the step (1.3) are: heating to 800°C at a rate of 5°C / min, then heating to 1780°C at a rate of 1°C / min; stopping heating, sintering at this temperature for 8h; then cooling to 300°C at a rate of 5°C / min, and then cooling naturally.
6. The method for preparing a YAG-derived glass optical fiber based on a multi-layer composite structure transparent ceramic according to claim 2, characterized in that: The specific parameters of the annealing treatment in the step (1.4) are as follows: heating at a rate of 5°C / min to 1450°C and keeping the temperature for 10 hours; cooling at a rate of 5°C / min to 300°C and then cooling naturally.
Citation Information
Patent Citations
A method for fabricating YAG-doped glass optical fibers
CN114409243B